Development of a computer-aided design environment for hardware oriented design - Hong, Teck Huat. (2008)
This research demonstrates how a hierarchical decomposition design process is being applied in an EDA environment to model a reprogrammable parallel hardware called the Reconfigurable Machine (RM). The RM is a massively parallel hardware which is built with a view of simulating various real-world applications in order to optimize their computations. Here, a three-layer backpropagation neural network is mapped onto the RM.